Pola Hidup Sehat Mahasiswa Pendidikan Jasmani STKIP Hermon Timika - Nurwirhanuddin; Maria Letisia; Suprianto; Habibi Sutirta; Herwin; Jhon Citro Trisakti; Nadira Jamco; Yoel Asril Sampe; Aschari Senjahari Rawe (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the healthy lifestyles of Physical Education students at STKIP Hermon Timika, in terms of hygiene, healthy food, regular lifestyle, increased endurance and physical fitness, disease prevention, increased intelligence and spirituality, healthy housing facilities, and health checks. The study used a quantitative descriptive design with a survey method. A sample of 50 students was determined using total sampling. The instrument was a 4-level Likert-scale questionnaire developed based on indicators of clean and healthy living behaviors, balanced nutrition guidelines, and promotive-preventive principles. Data were analyzed using descriptive statistics (means and percentages). The results indicate that students' healthy lifestyles are categorized as good to very good, with endurance and physical fitness scoring the highest (85%) and health checks scoring the lowest (60%). These findings indicate the need to strengthen preventive health interventions and access to regular health screening services on campus. Keywords: Students, Physical Education, PHBS, Healthy Lifestyle